The Conflict Between Tradition And Modernity In The Novel ‘Qandil Umm Hashem’ By Yehia Haqqi, A Critical Analytical Study - Wajih Abdel Fattah Matar (Ijaz Arabi Journal of Arabic Learning, 2023)
This research aims to analyze the civilizational conflict in Arabic literature, the novel “Qandil Umm Hashem” from an educational perspective. It explicitly attempts to state the advantages and disadvantages of the European countries' missions and their influence on the students. This influence has an internal psychological part and an external social part. The study also aims to equip the students with the essential tools to enable them how to deal with literary texts. The conflict between the ancient, represented in customs, habits, and inherited traditions, whether in science or aspects of life, has been opened for some of the Egyptian youth in specific and the Arab youth in general through scientific missions to European countries. The study has used the critical analytical method for content analysis. The research analyzes the novel's content and focuses on the issues under investigation. The results address the essential findings of the research they include that European countries missions influence the students both positively and negatively. The actions are ordered according to the Aristotelian triangle, meaning - beginning, middle, and end. The characters represent symbols that convey certain ideas. The civilization conflict is old and rooted and there is mutual hatred between the two cultures but there is no contradiction between science and religion.